2007
DOI: 10.1093/jac/dkm353
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of P-glycoprotein and multidrug resistance-associated proteins modulates the intracellular concentration of lopinavir in cultured CD4 T cells and primary human lymphocytes

Abstract: We provide evidence that lopinavir is a substrate of P-gp, MRP1 and MRP2. The intracellular concentration of lopinavir is increased when co-incubated with ritonavir, amprenavir and atazanavir in PBMCs. Manipulation of drug efflux transporters may be a useful strategy for increasing the intracellular concentration and thereby enhancing the clinical efficacy of lopinavir.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
85
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(90 citation statements)
references
References 33 publications
3
85
2
Order By: Relevance
“…OATP2B1 Kumar et al, 1999;Agarwal et al, 2007;Janneh et al, 2007;Weiss et al, 2007a;Hartkoorn et al, 2010;Kis et al, 2010;van Waterschoot et al, 2010 Nelfinavir CYP3A4/5 CYP2C19 ABCB1 ABCC1 ABCG2 OCT1 OCT2 OATP2B1 Kim et al, 1998b;Choo et al, 2000;Zhang et al, 2000;Baede-van Dijk et al, 2001;Jones et al, 2001a;Jones et al, 2001b;Gupta et al, 2004;Hirani et al, 2004;Salama et al, 2005;Kaddoumi et al, 2007;Weiss et al, 2007a;Hirt et al, 2008;Jung et al, 2008;Kis et al, 2010 Ritonavir CYP3A4/5 ABCB1 ABCC1 ABCC2 ABCG2 OCT1 OCT2 OATP2B1 Kumar et al, 1996;Koudriakova et al, 1998;Lee et al, 1998;Zhang et al, 2000;Jones et al, 2001a;Jones et al, 2001b;van der Sandt et al, 2001;Huisman et al, 2002;Gupta et al, 2004;Jung et al, 2008;Zastre et al, 2009;Kis et al, 2010 Saquinavir CYP3A4/5 ABCB1 ABCC1 ABCC2 ABCG2 OATP1A2 OATP1A3 OATP1B1 Fitzsimmons and Collins, 1997;Kim et al, 1998a,b;Kupferschmidt et al, 1998;Lee et al, 1998;Srinivas et al, 1998;…”
Section: Table 2 List Of the Main Drug Metabolism Enzymes (Cyp450 Andmentioning
confidence: 99%
See 2 more Smart Citations
“…OATP2B1 Kumar et al, 1999;Agarwal et al, 2007;Janneh et al, 2007;Weiss et al, 2007a;Hartkoorn et al, 2010;Kis et al, 2010;van Waterschoot et al, 2010 Nelfinavir CYP3A4/5 CYP2C19 ABCB1 ABCC1 ABCG2 OCT1 OCT2 OATP2B1 Kim et al, 1998b;Choo et al, 2000;Zhang et al, 2000;Baede-van Dijk et al, 2001;Jones et al, 2001a;Jones et al, 2001b;Gupta et al, 2004;Hirani et al, 2004;Salama et al, 2005;Kaddoumi et al, 2007;Weiss et al, 2007a;Hirt et al, 2008;Jung et al, 2008;Kis et al, 2010 Ritonavir CYP3A4/5 ABCB1 ABCC1 ABCC2 ABCG2 OCT1 OCT2 OATP2B1 Kumar et al, 1996;Koudriakova et al, 1998;Lee et al, 1998;Zhang et al, 2000;Jones et al, 2001a;Jones et al, 2001b;van der Sandt et al, 2001;Huisman et al, 2002;Gupta et al, 2004;Jung et al, 2008;Zastre et al, 2009;Kis et al, 2010 Saquinavir CYP3A4/5 ABCB1 ABCC1 ABCC2 ABCG2 OATP1A2 OATP1A3 OATP1B1 Fitzsimmons and Collins, 1997;Kim et al, 1998a,b;Kupferschmidt et al, 1998;Lee et al, 1998;Srinivas et al, 1998;…”
Section: Table 2 List Of the Main Drug Metabolism Enzymes (Cyp450 Andmentioning
confidence: 99%
“…A REVIEW OF HOST AND HIV VIRUS GENETIC VARIABILITY Several in vitro studies have shown that ABCC1 and ABCC2 transporters participate in the transport of protease inhibitors such as lopinavir, atazanavir, ritonavir, saquinavir, and indinavir (Srinivas et al, 1998;Jones et al, 2001b;Huisman et al, 2002;Dallas et al, 2004;Jorajuria et al, 2004;Agarwal et al, 2007;Janneh et al, 2007). Consequently, these transporters could be important modulators of the pharmacokinetics of these drugs by affecting their distribution in the body (van der Sandt et al, 2001;Huisman et al, 2002;Janneh et al, 2005Janneh et al, , 2007Anderson et al, 2006;Zastre et al, 2009).…”
Section: H Atp-binding Cassette Subfamily C Transporters (Multidrug mentioning
confidence: 99%
See 1 more Smart Citation
“…Because the equilibrium between extra-and intracellular concentrations is often regulated by efflux proteins, changes in efflux protein activity may alter the sensitivity of the cells to these compounds like it has been demonstrated for saquinavir, ritonavir, and lopinavir (12,18,19). Decreased intra-cellular availability of the drug in response to upregulation of efflux transporters will therefore shift IC 50 values for antiproliferative effects towards higher (extracellular) concentrations and thus protect the cells.…”
Section: Growth Inhibition Assaysmentioning
confidence: 99%
“…Most anti-HIV drugs act on intracellular targets (Owen and Khoo, 2004), and a high percentage of these drugs are substrates of some efflux transporters (Eilers et al, 2008;Janneh et al, 2005Janneh et al, , 2007Weiss et al, 2007;Hayashi et al, 2006). For the class of nucleoside reverse transcriptase inhibitors (NRTI), the current backbone of HAART, their pharmacological penetration into the target tissue/cells depends not only on the presence of transporters, but also on a cascade of intracellular activation (Painter et al, 2004).…”
Section: Introductionmentioning
confidence: 99%